Growth Strategies of A Freight Forwarder to A Logistics Service Provider through Supply Chain Collaboration - Mathew, Mithun (2009)
Due to globalization, shorter product life cycles, the global business networks have to be highly responsive to customer needs and the changing business environments. So in order to overcome these challenges, the organizations are bound to outsource the supporting services and to form partnerships and alliances to have a competitive advantage in the global market and to guarantee their survival. With respect to this much literature has been covered on the topic of Supply Chain Collaboration and has proved to be competitive advantage both in literature and topic. But what is Supply Chain Collaboration? How do firms actually collaborate? And what benefits can be gotten from forming such business relationships? The freight industry sector has been neglected in the modern research with limited literature. The international freight forwarders have become an important logistical intermediate that almost every company engages in international trade. The freight forwarders provide the logistics expertise. The research is meant to analyze the strategies for the growth of a local freight forwarder company into logistics service provider from the perspective of a forwarder through SC collaboration.